The Use Of Short Messaging Service (SMS) As a Supplementary Learning TooI Open University Malaysia (OUM) - Nurhizam , Safie (2004)
The objective of the research is to investigate the effectiveness usages of Short Messaging Service (SMS) As a Supplementary Learning TooI Open University Malaysia (OUM). The focus is on a project called mySMS, a service provide to learners in the coming 2004 August semester.